The effect of sports specialization on musculus quadriceps function after exercise-induced muscle damage - Skurvydas, A.; Brazaitis, M.; Venckunas, T.; Kamandulis, S.; Stanislovaitis, A.; Zuoza, A. (Applied Physiology, Nutrition, and Metabolism, 2011)
The primary aim of the present study was to examine the effect of eccentric exercise-induced (100 submaximal eccentric contractions at an angular velocity of 60°/s, with 20-s rest intervals) muscle damage on peripheral and central fatigue of quadriceps muscle in well-trained long-distance runners, sprint runners, volleyball players, and untrained subjects. We found that (i) indirect symptoms of exercise-induced muscle damage (prolonged decrease in maximal voluntary contraction, isokinetic concentric torque, and electrically induced (20 Hz) torque) were most evident in untrained subjects, while there were no significant differences in changes of muscle soreness and plasma creatine kinase 48 h after eccentric exercise between athletes and untrained subjects; (ii) low-frequency fatigue was greater in untrained subjects and volleyball players than in sprint runners and long-distance runners; (iii) in all subjects, electrically induced (100 Hz) torque decreased significantly by about 20%, while central activation ratio decreased significantly by about 8% in untrained subjects and sprint runners, and by about 3%-5% in long-distance runners and volleyball players. Thus, trained subjects showed greater resistance to exercise-induced muscle damage for most markers, and long-distance runners had no advantage over sprint runners or volleyball players.